2021
DOI: 10.1002/cphc.202100529
|View full text |Cite
|
Sign up to set email alerts
|

How Divalent Cations Interact with the Internal Channel Site of Guanine Quadruplexes

Abstract: The formation of guanine quadruplexes (GQ) in DNA is crucial in telomere homeostasis and regulation of gene expression. Pollution metals can interfere with these DNA superstructures upon coordination. In this work, we study the affinity of the internal GQ channel site towards alkaline earth metal (Mg2+, Ca2+, Sr2+, and Ba2+), and (post‐)transition metal (Zn2+, Cd2+, Hg2+, and Pb2+) cations using density functional theory computations. We find that divalent cations generally bind to the GQ cavity with a higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
11
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 59 publications
0
11
0
Order By: Relevance
“…Comparison with the 250 mM Mg­(ClO 4 ) 2 data showed that the perchlorate anion, ClO 4 – , has a slightly destabilizing effect compared to Cl – , probably due to weak interactions of this highly polarizable anion with nucleic acid bases . Not only salts but also organic osmolytes such as TMAO and crowding agents like Ficoll increased the stability and thus the melting temperature of the B-DNA, but the mechanism of stabilization may vary and depend on the concentration of the cosolute. …”
Section: Resultsmentioning
confidence: 96%
See 2 more Smart Citations
“…Comparison with the 250 mM Mg­(ClO 4 ) 2 data showed that the perchlorate anion, ClO 4 – , has a slightly destabilizing effect compared to Cl – , probably due to weak interactions of this highly polarizable anion with nucleic acid bases . Not only salts but also organic osmolytes such as TMAO and crowding agents like Ficoll increased the stability and thus the melting temperature of the B-DNA, but the mechanism of stabilization may vary and depend on the concentration of the cosolute. …”
Section: Resultsmentioning
confidence: 96%
“…The carbonylic oxygens of the guanine bases define a partially negatively charged channel in the core of G4Qs which, under biological conditions, host the monovalent alkali cations K + or Na + . Principally, divalent cations can also bind to the G4Qs’ cavity, even with higher affinity compared to conventional monovalent cations owing to more favorable electrostatic and orbital interactions . Displacement of the monovalent cations in vivo could lead to genotoxicity due to structural perturbation of telomeric and promotor regions, however.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Mg 2+ cations were found capable of placing themselves in the plane of the AGQ tetrad with a high binding ability compared to K + , which places itself in between the two tetrad planes. Several studies established that in the presence of cations, the guanine tetrad possesses extra stabilization energy, which results due to the change in its electronic environment. Since all-atomic MD simulation is insufficient to capture the charge delocalization, the hybrid QM/MM (quantum mechanical/molecular mechanical) MD simulations were performed. First two guanine tetrads of AGQ with the necessary metal ions (2 Mg 2+ ions3MAGQ, 1 K + ion2KAGQ, no cationAPO-AGQ) were treated with the SCC–DFTB level of QM theory, and the rest of the system was handled classically; atomic-level details of the QM region are shown in Figure A.…”
Section: Resultsmentioning
confidence: 99%
“…These planar structures furnish identical hydrogen‐bond energy trends as the non‐planar C 1 complexes (see Tables S2 and S3). The use of planar geometries allows for the separation of interactions within the σ and π electronic system which will become useful later on in this work [13b,f,14,15] …”
Section: Resultsmentioning
confidence: 99%